Customary Law of Larwul Ngabal in the Implementation of Regional Autonomy in North Moluccas - Bukido, Rosdalina; Rumkel, Nam; Wekke, Ismail Suardi; Palm, Elin (Faculty of Law, Hasanuddin University, 2018)
The Kei Islands of Southeast Moluccas, like other parts of Indonesia, have a customary order and cultural diversity. The values of local wisdom existing in the Kei community, which is contained in the customary law of Larwul Ngabal, is a very important cultural social capital in the social integration of its society. The type of study was an empirical research with sociological-anthropological juridical approach. The results show that the existence of customary law of Larwul Ngabal supports the implementation of regional autonomy with full authority and reinforcement in local regulations based on local wisdom in Kei Island. The dominant factors that caused the values of customary law of Larwul Ngabal have not provided legal strength in the implementation of local government is because it is determined by the recruitment factor of the leader who lacks capacity and competence. Added to the polarization of political parties and the values of local wisdom on financial strength in determining leadership. Therefore, to realize good local governance in Kei Islands, the values of customary law of Larwul Ngabal in various Local Regulations and local government policies must be accommodated, keeping in mind the custom, governmental and religious factors that are the foundation of Kei community life.